OBJEK WISATA RELIGI: MENELISIK SEJARAH DAN DAMPAK SOSIAL-EKONOMI BAGI MASYARAKAT LOKAL (STUDI KASUS PADA OBJEK WISATA BATU QUR’AN, PANDEGLANG): Religious Attractions: Examining History and Socio-Economic Impacts on Local Communities (Case Study on Batu Qur'an Tourism Object, Pandeglang) - Herdin Muhtarom; Jumardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Tourism is a sector that contributes to increasing national and regional income, it aims to increase development in Indonesia. Therefore, local tourism is a means to increase regional and national income. One of them is with local tourism, for example local tourism in Kadubumbang Village, Pandeglang Banten, namely Batu Qur'an religious tourism which has historical value and religious value. In this research, qualitative research is used in describing ideas that are in accordance with the object of research. With the Batu Qur'an tourism, it has an impact, especially for the local community, both in the social and economic fields in the Kadubumbang village area, Pandeglang Banten.